ARABIC AS A GLOBAL LANGUAGE (Academia Science Repository, 2023)
This article includes general information about the Arabic language as one of the most common languages in the world. The author considers some Arabic borrowings into Russian: algebra, ches t, genie, sheikh, etc. The study focuses on the grammatical features of the Arabic language and its current dialects.